The insertion of the highway Via Rápida (SC 446) and the challenges of urban expansion and environmental protection between Içara and Criciúma/SC (Research, Society and Development, 2020)
Mapping through satellite images is an important aid instrument related to urban areas and their respective infrastructures, where it allows the treatment of spatial information related to these areas and their specificities in an agile and precise way. The main objective of this study was the contextualization, mapping and analysis of the impacts caused by the insertion of the Aristides Bolan highway, better known as the highway, between the municipalities of Içara and Criciúma, located in the state of Santa Catarina. The highway work was inaugurated on December 20, 2017, so, as the construction is still recent, the impact that the insertion of the road generates between the municipalities and the emerging areas is slowly being perceived. According to the mapping and analysis of dense forest areas, urban infrastructure and agriculture and pasture, it was found that the implementation of the highway implied, during its construction, a change in the landscape to which it was inserted. Considering the results obtained, it was concluded that the Via-Fast, has significant impacts over the years in the urban space, can be positive or negative to the environment. The research sought to show that, although the highway has approximately 2 years of inauguration, over time it has had a major influence on the transformations in the surroundings.